Penerapan Teknik Audit Investigatif dalam Akuntansi Forensik untuk Mengungkap Fraud pada PT Dana Syariah Indonesia (DSI) - Siti Nur Azizah; Nensi Rahma Nor Hakiki; Trenda Indri Ardianti; Nanda Lutfiah Cahya May Salva; Tries Ellia Sandari (Jurnal Mahasiswa Manajemen dan Akuntansi, 2026)
This study examines the use of investigative audit techniques in forensic accounting to detect Fraud at PT Dana Syariah Indonesia (DSI), as indicated by delays in investor fund disbursement, inconsistencies in financial statements, and limited transparency in fund management. Using a descriptive qualitative approach through a literature review of relevant academic sources, the study finds that techniques such as follow the money, document and financial statement analysis, investigative interviews, and transaction pattern analysis are effective in uncovering complex and hidden Fraud. Moreover, forensic accounting strengthens these findings through in-depth financial analysis and the presentation of legally accountable evidence, demonstrating that the integration of both approaches is effective in revealing Fraud and enhancing transparency and accountability in financial management. The study also highlights the importance of strengthening internal control systems, improving corporate governance, and increasing supervision in financial institutions to minimize the risk of Fraudulent practices. In addition, the application of investigative audit techniques can support law enforcement processes by providing accurate and reliable evidence. Therefore, the implementation of forensic accounting and investigative audits is considered essential in maintaining public trust and ensuring the integrity of financial management within investment companies.